A Notes on the Blue-winged Teal (Spatula discors) and the influence of solar irradiance in a wetland from Boyacá State, Colombia - Fernando Ramírez (Rivista Italiana di Ornitologia - Research in Ornithology)
The Blue-winged Teal (Spatula discors) is a migratory species that has been observed in El Salitre wetland near Paipa (5° 46’48.47”N, 73°07’1.49”W), Boyacá State, Colombia. The number of individuals observed swimming in the open water and near the bank was counted from 6:00-8:00 am, 10:00-12:00 pm, and 4:00-6:00 pm. The amount of solar irradiance was recorded as a daily mean from 25% (mean 148.5 watts/m2) to 100% (mean 594 watts/m2) from a nearby weather station. The greatest number of ducks (mean = 62.57) was observed from 4:00 to 6:00 pm. Overall, the number of ducks was greater during low solar irradiance conditions (25%). In contrast, a lower number of ducks were observed at higher irradiance levels (75 and 100%). El Salitre wetland is an important site for the conservation of the Blue-winged Teal as well as other aquatic bird species.